Preserving Ghana’s Water Resources: Insights from Communities Along Keta Lagoon Complex Ramsar Site - Torsu, Leonard Atsu (MultiTech Publisher, 2024)
Maintaining water resources in Ghana is crucial to the survival of its populace. It is commonly said, it is the “survival of the fittest”, but it is water that makes it possible for the fittest to survive. This study examined Ghanaians’ activities towards water resources by exploring the views of residents of Anyanui, Anloga and Tegbi along Keta Lagoon Complex Ramsar Site. The study adopted the qualitative approach, narrative design and thematic analysis. In-depth face-to-face interviews with 15 residents, purposively and conveniently sampled from the three communities and observations in the Anloga District revealed that, there is a moderate environmental challenge to Keta Lagoon Complex Ramsar site. Over exploitation of mangroves, the habit of open defecation, dumping of refuse in the enclave and poaching were revealed in the study. The study concludes that, advancing the protection and strategizing to achieve effective management of wetlands in Ghana is needed to ensure that ecosystem benefits inure to mankind. Based on this, the study recommends that, Traditional chiefs should be given the mandate and be tasked to ensure rules and regulations regarding Ramsar sites are well respected. Moreover, Wildlife Division/Forestry Commission needs to be more vibrant in ensuring that, wetlands are wisely used and protected. The study also recommends that, toilet facilities need to be provided along the banks of the Keta Lagoon Complex Ramsar Site